Gender Differences in Implementing Organizational Change in Romania’s Central Public Administration - Constantin M. Profiroiu; Alina G. Profiroiu; Corina C. Nastaca (Central European Public Administration Review)
The present study analyses the gender differences in implementing organizational change in Romania’s central public administration, from a subordinates’ perspective, in order to establish whether female leaders are more likely to adopt change in comparison to their male counterparts. The research methodology consists of an opinion survey conducted in the central public administration of Romania based on a questionnaire. The study reveals that female leaders are perceived in a positive, yet not in a better manner than men. They are considered transformational leaders capable of involvement in the process of organizational change of public institutions. There are no significant differences between the perceptions of men and women as leaders, although almost all the differences are in favour of men. The study shows a strong correlation between transformational leadership and leaders’ capacity of implementing the management of change, the relationship being stronger in the case of female leaders who should continue to strengthen transformational behaviours.